2009
DOI: 10.1002/rmv.630
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and autophagy

Abstract: SUMMARY Autophagy is an evolutionarily conserved intracellular process by which bulk cytoplasm is enveloped inside a double-membraned vesicle and shuttled to lysosomes for degradation. Within the last 15 years, the genes necessary for the execution of autophagy have been identified and the number of tools for studying this process has grown. Autophagy is essential for tissue homeostasis and development and defective autophagy is associated with a number of diseases. As intracellular parasites, during the cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
220
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(224 citation statements)
references
References 118 publications
(171 reference statements)
3
220
1
Order By: Relevance
“…Initially, autophagy functions are as a tumor suppressor and later, when HCC has developed, the autophagy may contribute to its growth [303,305] . Microbes have evolved mechanisms to evade and exploit autophagy and both HBV and HCV use autophagy for their own survival [306] . Studies have shown that autophagy enhances viral replication at most steps of HBV replication and that autophagy proteins are likely to be factors for the initial steps of HCV replication [307,308] .…”
Section: Resultsmentioning
confidence: 99%
“…Initially, autophagy functions are as a tumor suppressor and later, when HCC has developed, the autophagy may contribute to its growth [303,305] . Microbes have evolved mechanisms to evade and exploit autophagy and both HBV and HCV use autophagy for their own survival [306] . Studies have shown that autophagy enhances viral replication at most steps of HBV replication and that autophagy proteins are likely to be factors for the initial steps of HCV replication [307,308] .…”
Section: Resultsmentioning
confidence: 99%
“…Selective forms of autophagy mediate degradation of specific damaged organelles: mitochondria (mitophagy), ER (ER-phagy), peroxysomes (pexophagy), ribosomes (ribophagy) and intracellular pathogens (xenophagy) [26][27][28][29][30]. Given the paramount multifacetal roles of mitochondria, selective autophagic removal of dysfunctional mitochondria, mitophagy, is attracting increasing interest.…”
mentioning
confidence: 99%
“…However, the microbes have also evolved mechanism to evade and exploit autophagy and both HBV and HCV have adapted to use autophagy for their own survival. 66 HCV utilizes various autophagy components for its own replication. 67 Studies have shown that there is an accumulation of autophagic vacuoles in HCV-infected hepatocytes; however this autophagy is inefficient as the autophagosomes are not able to increase autophagic protein degradation.…”
Section: Targeting Autophagy In Infective Diseases: Hepatitis B Virusmentioning
confidence: 99%